Demand analysis of beef in Malaysia - Ismail, Nur Syakirah (2018)
The purpose of this study is to analyse the current market growth, meat consumption of beef and the elasticity of beef towards price of beef, price of mutton, price of chicken and income. An econometric model was set up for analysis of demand for beef in Malaysia. Secondary data was used and it is obtained mainly from the Department of Veterinary Services. Time series data covering the period of 1988-2017 (30 years) was use for this analysis. The overall demand models are generally quite satisfactory with an R2 value of 0.941. Demand elasticity shows that beef is an inelastic product, which means that the consumption will not be highly influenced by the changes of the price of beef in market. The results also indicate that mutton and chicken are substitutes to beef. The beef meat also is a normal good as proven by the positive results from income elasticity. The consumption of beef is influence by many factors such as religion, lifestyles, habits as well as the availability of the beef meat itself. Besides that, the current growth market for variety of meat like beef, mutton and chicken are on an increasing growth trend.